A Novel Three-Dimensional Computational Method to Assess Rod Contour Deformation and to Map Bony Fusion in a Lumbopelvic Reconstruction After En-Bloc Sacrectomy - Eltes, Peter Endre; Turbucz, Mate; Fayad, Jennifer; Bereczki, Ferenc; Szőke, György; Terebessy, Tamás; Lacroix, Damien; Varga, Peter Pal; Lazary, Aron (Frontiers in Surgery, 2022)
Introduction En-bloc resection of a primary malignant sacral tumour with wide oncological margins impacts the biomechanics of the spinopelvic complex, deteriorating postoperative function. The closed-loop technique (CLT) for spinopelvic fixation (SPF) uses a single U-shaped rod to restore the spinopelvic biomechanical integrity. The CLT method was designed to provide a nonrigid fixation, however this hypothesis was not been previously tested. Here, we establish a computational method to measure the deformation of the device and characterize the fusion process based on the 6-year follow-up (FU) data. Materials and Methods Post-operative CT scans were collected from a male patient who underwent total sacrectomy at the age of 42 due to a chordoma. CLT was used to reconstruct the spinopelvic junction. We defined the 3D geometry of the implant construct. Using rigid registration algorithms, a common coordinate system for the CLT was created in order to measure and visualise the deformation of the construct during the FU. In order to demonstrate the cyclical loading of the construct, the patient underwent gait analysis at the 6th year FU. First, a region of interest (ROI) was selected at the proximal level of the construct, then the deformation was determined during the follow-up period. In order to investigate the fusion process, a single axial slice-based voxel finite element (FE) mesh was defined. The Hounsfield values (HU) were determined and using an empirical linear equation, bone mineral density (BMD) values were assigned for every mesh element, out of ten colour-coded categories (1st category =0 g/cm3, 10th category 1,12 g/cm3). Results Significant correlation was found between days passed postoperatively and sagittal plane deformation, resulting in a forward bending tendency of the construct. Volume distributions were determined and visualised over time for the different BMD categories and it was found that the highest BMD value volume in the first postoperative CT was 0.04 cm3, at the 2nd year FU was 0.98 cm3, and after 6 years it was 2.30 cm3. Conclusion The CLT provides a nonrigid fixation. The quantification of the implant deformation and bony fusion may help in the understating of the complex lumbopelvic biomechanics after sacrectomy.